Fatores associados à resposta imunológica paradoxal ao tratamento antirretroviral em pacientes com aids em ambulatório de doenças infecciosas - Casotti, Janaina Aparecida Schineider (2010)
Highly Active Antiretroviral Therapy (HAART) had an important role in the reduction of morbidity and mortality in AIDS, decreasing the plasma HIV viral load (HIVVL) and increasing the T-CD4 + lymphocyte count (CD4). Paradoxical immune response (PIR) is defined as the absence of immune response in patients with undetectable HIVVL for over a year. Its prevalence ranges from 8 to 42%, and has been associated with multiple risk factors. This study aims to verify the prevalence of PIR and to identify factors associated with this kind of response. Two methods were used: a cross-sectional study to determine the prevalence and a case-control study to verify the presence of risk factors. The site of the study was the Infectious Diseases Clinic of the Hospital Universitário Cassiano Antonio Moraes in Vitória – ES – Brazil, with 934 patients on HAART. Data were collected from April to September 2009 and it was used a standardized form, previously tested, containing the study variables. Cases were patients with PIR, defined as CD4 <350 cells/mm3 and undetectable viral load, on HAART for at least one year. Controls were patients with CD4 counts ≥350 cells/mm3 and undetectable viral load, on HAART for at least one year. The eligibility criteria differed a little between cross-sectional and case-control studies. The study was approved by the Committee of Ethics on Research of the Center of Health Sciences of the Universidade Federal do Espírito Santo. For the statistical analysis, the methods used were: a descriptive approach and univariate and multivariate analysis by binary logistic regression. Results of the cross-sectional study revealed a prevalence of 9% (95% Confidence Interval: 6.6% to 11.4%). For the case-control study, 39 patients met the eligibility criteria and were matched with 160 controls. Variables with p <0.1 were entered into a statistical model following a hierarchical theoretical tree built to identify the factors associated with the PIR. Variables that remained significant were: total time in months on HAART [odds ratio (OR) = 0,981, 95% confidence interval (CI): 0,96-0,99], the absolute value of the lowest count of CD4 cells already registered in the patient (nadir CD4) [OR = 0.985, 95% CI: 0.97-0.99], and the time (in months) of undetectable HIV viral load [OR = 0.969, 95% CI: 0.94-0.99). The prevalence was similar to that previously reported in the literature. Regarding the risk factors, it was observed that the time under HAART, the lowest value of nadir CD4 and the time of undetectable HIVVL were protective factors. For each additional month in the duration of medication use and in the duration of time of undetectable HIVVL, occurs a decrease of 1.9% and 3.1% in the risk of PIR, respectively. For every one cell increase in the count of nadir CD4 cells, occurs a decrease in the risk of RIP of 1.5% or, alternatively, for every 100 cells increase in nadir CD4 cells, there is a decrease of 77.7% in the risk of PIR. Adherence to treatment can be considered a factor indirectly related to the occurrence of PIR if one considers that the longer the duration of undetectable HIVVL, the lower the risk of RIP. It is possible to infer that avoiding delay in the starting of HAART until very low CD4 counts can reduce the occurrence of PIR, supporting the new considerations about starting HAART with higher CD4 cell counts.